PENGARUH MEDIA TANAM DAN PEMBERIAN PUPUK UREA TERHADAP PERTUMBUHAN DAUN BIBIT KELAPA SAWIT (Elaeis gueneensis Jacq.) DI MAIN NURSERY - Waruwu, Erwin; Sijabat, Octanina Sari; Kurniawan, Dedi; Berliana, Yunida (LPPM Universitas Katolik Santo Thomas Medan, 2023)
The oil palm plant (Elaeis guineensis Jacq.) originates from West Africa, is the mainvegetable oil producing plant which has a higher productivity than other vegetable oil producing plants. This study aims to determine the effect of nitrogen fertilizer application onthe number of leaves and stem diameter of oil palm seedlings. The study used a factorialrandomized block design (RBD) with 2 treatment factors, namely the planting mediafactor and the urea fertilizer application factor. The results of the analysis showed that thetreatment of the growing media had a significant effect on the number of leaves. The ureatreatment showed no significant effect on the number of leaves and the interaction of thetwo factors had no significant effect on the number of leaves.